THE INFLUENCE OF LIFESTYLE AND FINANCIAL TECHNOLOGY ON FINANCIAL BEHAVIOR OF SHOPEE PAYLATER USERS AMONG UMMI STUDENTS - Annisa Ayulestari Noer; Nor Norisanti; Kokom Komariah (Multidiciplinary Output Research For Actual and International Issue (MORFAI), 2025)
This study aims to analyze the influence of lifestyle and financial technology on financial behavior among Shopee PayLater users among students of Universitas Muhammadiyah Sukabumi (UMMI). The background of this study is based on the increasing use of digital financial services such as Shopee PayLater which facilitates transactions, but has the potential to encourage consumptive behavior and unwise financial management, especially among students who are in the transition phase towards financial independence. This study uses a quantitative approach with a causal associative descriptive method. The sample used was 367 respondents who were active UMMI students who used the Shopee PayLater service, and was determined using the Slovin formula. Data collection was carried out through questionnaires and analyzed using multiple linear regression, as well as validity, reliability, classical assumptions, t-tests (partial), and F-tests (simultaneous). The results of the study showed that partially lifestyle had a significant effect on financial behavior, with a calculated t value greater than the t table. Likewise, financial technology also has a significant effect on financial behavior. Simultaneously, both variables had a significant effect on students' financial behavior, with an R² value of 0.513. This shows that 51.3% of the variation in students' financial behavior can be explained by lifestyle and use of financial technology. This study emphasizes the importance of financial literacy in dealing with easy access to digital credit services so that students are able to make wise financial decisions in today's technological era. This study aims to analyze the influence of lifestyle and financial technology on financial behavior among Shopee PayLater users among students of Universitas Muhammadiyah Sukabumi (UMMI). The background of this study is based on the increasing use of digital financial services such as Shopee PayLater which facilitates transactions, but has the potential to encourage consumptive behavior and unwise financial management, especially among students who are in the transition phase towards financial independence. This study uses a quantitative approach with a causal associative descriptive method. The sample used was 367 respondents who were active UMMI students who used the Shopee PayLater service, and was determined using the Slovin formula. Data collection was carried out through questionnaires and analyzed using multiple linear regression, as well as validity, reliability, classical assumptions, t-tests (partial), and F-tests (simultaneous). The results of the study showed that partially lifestyle had a significant effect on financial behavior, with a calculated t value greater than the t table. Likewise, financial technology also has a significant effect on financial behavior. Simultaneously, both variables had a significant effect on students' financial behavior, with an R² value of 0.513. This shows that 51.3% of the variation in students' financial behavior can be explained by lifestyle and use of financial technology. This study emphasizes the importance of financial literacy in dealing with easy access to digital credit services so that students are able to make wise financial decisions in today's technological era.